Risk Factor for Relapse in Childhood Nephrotic Syndrome - A Hospital Based Retrospective Study (Faridpur Medical College Journal, 2012)
Nephrotic Syndrome (NS) is a common childhood illness characterized by massive proteinuria, hyperlipidemia, hypoalbuminemia & edema. NS is a disease of relapse and it is a major problem to manage the cases with frequent relapse. So it is very important to find out such children who are prone to develop frequent relapse. This retrospective study was conducted in the paediatric department of Dhaka Medical College Hospital (DMCH) from January to December 2005.Total 100 children with relapsed NS of them 50 had Frequent Relapse NS (FRNS) and 50 had Infrequent Relapse NS (IFRNS) were included in the study with a view to find out the risk factors for relapse. Data were collected from previous medical and hospital records. Data were analyzed by using SPSS program. Chi-squared test and Student's t-Test were used as statistical test and p value < 0.05 was taken as significant. NS was more common among 2-6 years of age (67%) with male to female ratio roughly 2:1. Most of patient with frequent relapse had age